THE INFLUENCE OF CAREER DEVELOPMENT, INCENTIVES AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE IN JOB SATISFACTION INTERVENTION - Mardiana; Ngaliman; Sri Yanti (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
Abstract-Employee performance at the District Regional Secretariat Karimun experience decline between 2022 to 2024, which is seen from indicator Report Accountability Regional Government and Index Professionalism Bureaucracy. Level of satisfaction work also shows decline, reflected from height number absence employee. Development stagnant career and unmet incentives​​ satisfying, result delay during three year Lastly, also contribute to problem this. Besides that, the atmosphere environment work is also lacking harmonious. Mixed method research This limited and intended for research influence development career, incentives and environment Work to performance in intervening satisfaction work. It is hoped that the study scientific This can strengthen existing theories and provide​ more information​ accurate about intervening role of satisfaction work on relationships between development career, incentives, and environment Work to performance. The main data collection analyzed with Smart Partial Least Square application uses all over population employees (Census), at the Secretariat District Government​ Karimun, which has 141 employees. It was concluded that development career influential positive significant to performance and satisfaction Work employees, while incentive own influence positive No significant. Environment Work influential negative significant to performance but positive significant to satisfaction work. Satisfaction work also has an effect positive significant to performance employee. Development career and environment Work in a way positive significant influence performance employees in intervening satisfaction work . Meanwhile incentive influential positive No significant to performance employee. It is recommended that the Karimun Regency Regional Secretariat implement a structured career development program and review the reward and benefit system to ensure transparency and timely disbursement. Create a conducive work environment through good communication and team-building activities.